Stock Return Expectations in the Credit Market - Hans Byström (Lund University, School of Economics and Management, Department of Economics, 2016)
In this paper we compute long-term stock return expectations (across the business cycle) for individual firms using information backed out from the credit derivatives market. Our methodology builds on previous theoretical results in the literature on stock return expectations and, empirically, we demonstrate a close relationship between credit-implied stock return expectations and future realized stock returns. We also find stock portfolios selected based on credit-implied stock return forecasts to beat equally- and value-weighted portfolios of the same stocks out-of-sample. Contrary to many other studies, our expectations/predictions are made at the individual stock level rather than at the portfolio level, and no parameter estimations using historical stock price- or credit spread observations are needed.
Keywords: G01; G10; 330; stock market; credit default swap; implied volatility; CreditGrades; return expectations